X-Ray image detector based on light guides and scintillators - Rocha, J. G. (2009)
This paper reports on a study concerning the design of an X-ray detector that is suitable to analyze a small area with high spatial resolution. The indirect method of X-ray detection is used, i.e., the X-rays are first converted into visible light, which is then detected. In this design, an array of CsI:Tl scintillators, encapsulated by aluminum walls, is coupled with an array of CMOS photodetectors. This structure, patented and described theoretically by the authors in previous works, can be obtained using the SU-8 negative photoresist as a sacrificial layer. The experimental work consisted in the deposition of a scintillator layer, and an aluminum layer on the active area of a commercially available digital imaging sensor, thus supporting the developed detector design. X-ray imaging tests were performed using the PHILIPS X’Pert equipment. Promising results were obtained, featuring high resolution and detail.